Deadwood : The Complete First Season Disc 1 - Almereyda, Michael; McShane, Ian.; Jim Beaver; Molly Parker; Timothy Olyphant Robin Weigert (USA Home Box Office (HBO), 2004)
The town of Deadwood, South Dakota in the weeks following the Custer massacre is a lawless sinkhole of crime and corruption. Into this uncivilized outpost ride a disillusioned and bitter ex-lawman, Wild Bill Hickok, and Seth Bullock, a man hoping to find a new start for himself. Both men find themselves quickly on opposite sides of the legal and moral fence from Al Swearengen, saloon owner, hotel operator, and incipient boss of Deadwood. The lives of these three intertwine with many others, the high-minded and the low-lifes who populate Deadwood in 1876.
A show set in the late 1800's, revolving around the characters of Deadwood, South Dakota; a town of deep corruption and crime.
Language : English Subtitles : English
Keywords: Adventure -- Crime -- Western -- History -- Drama; Tv Series